Does Economic Growth Interact With The Basic Sector, Human Development, and Provincial Minimum Wage on Poverty in Sumatra Island Provinces? - Zulha, Arienal Martha; Silvia, Vivi; Abrar, Muhammad (Politeknik Siber Cerdika Internasional, 2024)
A high level of poverty in an area can have a significant impact on the economic performance of a region. This study will analyze the influence of the base sector, human development, and provincial minimum wage on poverty through the role of GDP growth in Sumatra. The ARDL and Location Quotient (LQ) panel data regression methods were used to analyze panel data consisting of 10 provinces in Sumatra for the period 2011 to 2022. The findings found that there is one sector that is dominant in all provinces on the island of Sumatra, namely the Agriculture, Fisheries, and Forestry sectors. The direct influence between the variables of the base sector, human development, and regional minimum wage on poverty and economic growth shows that in the long run, human development and the minimum wage have a negative effect on poverty and economic growth in a positive direction, while the base sector has no effect on poverty and economic growth. Economic growth plays a mediating role in mediating the three variables. The government, in reducing poverty and encouraging inclusive economic growth, is advised to allocate greater resources and investment to the agriculture-based sectors, and the government can also focus policies on increasing human development and minimum wage, considering that these variables have proven to have a positive influence on economic growth directly.